Językowe sposoby kreowania nazw ras psów w socjolekcie miłośników psów (uwagi na podstawie materiału zebranego z forów internetowych przeznaczonych dla miłośników psów) - Klauze, Małgorzata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
This article presents the linguistic ways of creating names of dog breeds for dog lovers. The research material comes from online forums associating dog lovers. This article is just an introduction to the deliberations on one of the environmental variations of the language, that is the language of dog lovers.